Casein phosphopeptides and CaCl2 increase penicillin production and cause an increment in microbody/peroxisome proteins in Penicillium chrysogenum - Domínguez-Santos, Rebeca; Kosalková, Katarina; García-Estrada, Carlos; Barreiro, Carlos; Ibáñez, Ana; Morales, Alejandro; Martín, Juan-Francisco (Journal of proteomics, 2017)
Transport of penicillin intermediates and penicillin secretion are still poorly characterized in Penicillium chrysogenum (re-identified as Penicillium rubens). Calcium (Ca2+) plays an important role in the metabolism of filamentous fungi, and casein phosphopeptides (CPP) are involved in Ca2+ internalization. In this study we observe that the effect of CaCl2 and CPP is additive and promotes an increase in penicillin production of up to 10–12 fold. Combination of CaCl2 and CPP greatly promotes expression of the three penicillin biosynthetic genes. Comparative proteomic analysis by 2D-DIGE, identified 39 proteins differentially represented in P. chrysogenum Wisconsin 54-1255 after CPP/CaCl2 addition. The most interesting group of overrepresented proteins were a peroxisomal catalase, three proteins of the methylcitrate cycle, two aminotransferases and cystationine β-synthase, which are directly or indirectly related to the formation of penicillin amino acid precursors. Importantly, two of the enzymes of the penicillin pathway (isopenicillin N synthase and isopenicillin N acyltransferase) are clearly induced after CPP/CaCl2 addition. Most of these overrepresented proteins are either authentic peroxisomal proteins or microbody-associated proteins. This evidence suggests that addition of CPP/CaCl2 promotes the formation of penicillin precursors and the penicillin biosynthetic enzymes in peroxisomes and vesicles, which may be involved in transport and secretion of penicillin. Penicillin biosynthesis in Penicillium chrysogenum is one of the best characterized secondary metabolism processes. However, the mechanism by which penicillin is secreted still remains to be elucidated. Taking into account the role played by Ca2+ and CPP in the secretory pathway and considering the positive effect that Ca2+ exerts on penicillin production, the analysis of global protein changes produced after CPP/CaCl2 addition is very helpful to decipher the processes related to the biosynthesis and secretion of penicillin. [Display omitted] •Casein phosphopeptides (CPP) and calcium (CaCl2) increase penicillin production.•These compounds exert a synergistic effect at different subcellular levels.•The expression of penicillin biosynthetic genes is strongly stimulated by CPP/CaCl2.•Most of the proteins induced by CPP/CaCl2 are peroxisomal or microbody-associated.